Integrative Treatment of Reflux and Functional Dyspepsia in Children - Ann Ming Yeh; Brenda Golianu (MDPI AG, 2014)
Gastroesophageal reflux disease (GERD) and functional dyspepsia (FD) are common problems in the pediatric population, with up to 7% of school-age children and up to 8% of adolescents suffering from epigastric pain, heartburn, and regurgitation. Reflux is defined as the passage of stomach contents into the esophagus, while GERD refers to reflux symptoms that are associated with symptoms or complications-such as pain, asthma, aspiration pneumonia, or chronic cough. FD, as defined by the Rome III classification, is a persistent upper abdominal pain or discomfort, not related to bowel movements, and without any organic cause, that is present for at least two months prior to diagnosis. Endoscopic examination is typically negative in FD, whereas patients with GERD may have evidence of esophagitis or gastritis either grossly or microscopically. Up to 70% of children with dyspepsia exhibit delayed gastric emptying. Treatment of GERD and FD requires an integrative approach that may include pharmacologic therapy, treating concurrent constipation, botanicals, mind body techniques, improving sleep hygiene, increasing physical activity, and traditional Chinese medicine and acupuncture.